2013
DOI: 10.1111/1755-0998.12182
|View full text |Cite
|
Sign up to set email alerts
|

Species discrimination in Sisyrinchium (Iridaceae): assessment of DNA barcodes in a taxonomically challenging genus

Abstract: DNA barcoding aims to develop an efficient tool for species identification based on short and standardized DNA sequences. In this study, the DNA barcode paradigm was tested among the genera of the tribe Sisyrinchieae (Iridoideae). Sisyrinchium, with more than 77% of the species richness in the tribe, is a taxonomically complex genus. A total of 185 samples belonging to 98 species of Sisyrinchium, Olsynium, Orthrosanthus and Solenomelus were tested using matK, trnH-psbA and internal transcribed spacer (ITS). Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 67 publications
(200 reference statements)
2
36
0
Order By: Relevance
“…However, ITS region has proved to be a suitable marker in authentication of Cassia species in the commercial herbal market (Seethapathy et al, 2014). The strong identification ability of nuclear region ITS have been verified in many complex groups (Baldwin et al, 1995; Alves et al, 2014; Wang et al, 2014; Giudicelli, Mäder & De, 2015). Therefore, we suggest that ITS1 itself could be the first option for DNA barcoding in subtribe Cassiinae, though ITS2 should not be discarded.…”
Section: Discussionmentioning
confidence: 93%
“…However, ITS region has proved to be a suitable marker in authentication of Cassia species in the commercial herbal market (Seethapathy et al, 2014). The strong identification ability of nuclear region ITS have been verified in many complex groups (Baldwin et al, 1995; Alves et al, 2014; Wang et al, 2014; Giudicelli, Mäder & De, 2015). Therefore, we suggest that ITS1 itself could be the first option for DNA barcoding in subtribe Cassiinae, though ITS2 should not be discarded.…”
Section: Discussionmentioning
confidence: 93%
“…However, these suggested DNA barcodes, matK , rbcL , psbA‐trnH , and ITS, are not effective enough to discriminate closely related or recently diverged species (Newmaster et al, ; Newmaster & Subramanyam, ), especially in certain species‐rich genera (Yan et al, ). For example, Alves et al () used three DNA barcodes (ITS, matK , and psbA ‐ trnH ) to identify the previously named species in the genus Sisyrinchium L. (Iridaceae). They found that only 20% or 39% of sampled species could be identified by two plastid barcodes or ITS, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Within the past century, species of this genus have undergone additional fragmentation due to human activities, which has resulted in isolated subpopulations. The study of the genus Sisyrinchium is highly complex owing to the lack of reliable morphological apomorphies (Henderson, 1976), unresolved phylogenetic relationships at the species level (Chauveau et al, 2011;Karst and Wilson, 2012), reticulate evolution driven by polyploidy (Tacuatiá et al, 2012a,b;Alves et al, 2014), and hybridization (Henderson, 1976;Cholewa and Henderson, 1984;Yamaguchi and Hirai, 1987). The most complete phylogenetic study of Sisyrinchium performed by Chauveau et al (2011) strongly suggests that species classified in section Hydastylus and section Viperella belong to a single group of plants that has undergone a recent adaptive radiation (Clade IV).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the putative occurrence of incomplete lineage sorting within this clade may be partly explained by the low level of discrimination observed between species. Furthermore, Alves et al (2014) also had difficulties assigning species identifications in this taxonomic group using plant barcode markers (ITS, matK, and trnH-psbA). The authors suggest natural hybridization as one possible explanation because it can reduce the efficiency of DNA barcoding since it generally fails to identify species undergoing extensive reticulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation